Budidaya Tanaman Hidrophonik Asman Toga “Terollas” sebagai Inovasi Media Tanam di Desa Kalidawir Sidoarjo - Dianita Agil Insani; M. Firman Fachrizzal; Tofan Tri Nugroho (LP2M Universitas Muhammadiyah Enrekang, 2022)
Many people in Kalidawir village, Tanggulangin district, Sidoarjo district still use the asman toga through land media in front of their house. As time goes by, the land as a planting medium is getting narrower due to the increasing number of buildings that stand to replace the function of land for cultivation. The existence of new innovations in the form of hydrophonic planting media is expected to be able to answer that challenge. The method used in the implementation of this hydrophonic plant is ABCD (Asset Based Community Development) by utilizing local assets in the form of an abandoned hydrophonic chart at the Kalidawir village hall. This cultivation is very useful as an effort to reduce operational costs but can optimize crop yields. Asman toga hydrophonic plant cultivation training is carried out in the UMSIDA KKN – T program as a form of community service application, where students can apply the theory that has been obtained so that it can be applied in real time in Kalidawir village, Sidoarjo. The results of the implementation of the KKN – T activity can be seen from the increasing number of Asman Toga hydrophonic plants in the yards of residents' houses and the use of organic fertilizers as an environmentally friendly hydrophonic plant fertilizer.